Enhancing Numeracy Literacy through CBL-STEM: Developing Differentiated Learning Materials with Augmented Reality and Articulate Storyline Integration - Ananda Verry Setiawan; Selva Ayu Meilina; Stefany Margaretha Hutauruk; Fadhila Salvia Khairunnisa; Alfina Nur Arofah; Adi Satrio Ardiansyah (STAI Hubbulwathan Duri, 2024)
Numeracy literacy is a critical skill for solving real-world problems, yet it remains low among students in Indonesia. This study aims to address this issue by developing Challenge-Based Learning (CBL)-STEM learning materials tailored to differentiated learning styles and integrated with Articulate Storyline and Augmented Reality (AR). This Research and Development (RD) study utilized cluster random sampling and employed tests, questionnaires, and interviews for data collection. Data analysis was conducted using descriptive quantitative and qualitative techniques. The feasibility, readability, and student response tests scored averages of 93.38%, 88.13%, and 87.27%, respectively, demonstrating the effectiveness of the developed materials. The CBL model presented real-life challenges, while the STEM approach integrated science, technology, engineering, and mathematics to create meaningful learning experiences. These materials significantly enhanced numeracy literacy among students. The integration of CBL-STEM with technologies such as Articulate Storyline and AR proved highly feasible and effective. Students found the materials easy to understand and engaging, indicating a positive reception. This approach highlights the potential of innovative, tech-integrated learning solutions in addressing Indonesia’s numeracy literacy challenges. CBL-STEM learning materials incorporating Articulate Storyline and AR are highly effective and practical for improving numeracy literacy. This innovation demonstrates promise for broader applications, with the potential to address low numeracy literacy in Indonesia on a larger scale by integrating additional technologies.